Radical innovation and its regional impact—a roadmap for future research - David Audretsch; Dirk Fornahl; Torben Klarl (Small Business Economics, 2021)
The aim of this paper is to introduce the special issue of Small Business Economics on "Radical Innovation, Entrepreneurship, and (Regional) Growth" and present a roadmap for future research in the area. This article argues that the link between the literature on radical innovation, entrepreneurship, and (regional) growth is still an underresearched topic. This paper also reviews the special issue's contributions that allow for a more nuanced understanding of this important link.
Keywords: O31; O32; O38; L26; 330; Radical innovation; Entrepreneurship; Regional growth